Eksistensi Penerapan Penjatuhan Hukuman Mati di Indonesia Terhadap Kejahatan Narkotika di Indonesia - Valedra Sitorus, Juan; Firmansyah, Hery (Universitas Ekasakti, 2023)
The implementation of the death penalty in Indonesia is something that is seen as contrary to humanity and human rights. The death penalty in Indonesia is still used, but its application is only used for certain types of crimes. The existence of the death penalty is still widely discussed in the national and international realm, as is whether the death penalty still needs to be applied to be used as punishment for a crime.